Critical illness myopathy: Sepsis-mediated failure of the peripheral nervous system - Friedrich, Oliver (European Journal of Anaesthesiology, 2008)
With better survival of critically ill patients, 'de novo' arising neuromuscular complications like critical illness myopathy or polyneuropathy have been increasingly observed. Prolonged hospitalization not only imposes risks like pneumonia or thrombosis on patients but also represents a real budget threat to modern intensive-care medicine. Clinical symptoms like muscle weakness and weaning failure are common to critical illness myopathy and critical illness polyneuropathy and do not allow for distinction. Specific therapies are not yet available, and the quest for the pathomechanisms has proved more complicated than anticipated. Especially for critical illness myopathy, multiple sites of disturbances to the excitation-contraction coupling cascade are possible causes of muscle weakness. The present review summarizes the epidemiological, clinical and diagnostic features of critical illness myopathy and then focuses on current concepts of the presumed pathomechanisms of critical illness myopathy. Sepsis was shown to be a major cause of critical illness myopathy and special emphasis will be placed on how sepsis and inflammatory mediators influence (i) the membrane excitability at the level of voltage-gated ion channels and (ii) the intracellular protein signalling that results in selective loss of myosin protein content and muscle wasting. For (i), critical illness myopathy represents a new type of acquired channelopathy affecting the inactivation properties of Na channels. For (ii), both protein proteolysis and protein build up at the transcriptional level seem to be involved. Findings from different studies are put into a common context to propose a model for cytokine-mediated failure of muscle in severe sepsis. This can open a series of new possible trials to test specific therapeutic strategies in the future. © 2008 European Society of Anaesthesiology.
Keywords: Critical care; Mucular diseases; Myopathy; Neuromuscular diseases; Polyneuropathy; Sepsis